An Improved Hybrid Cloud Computing Security Architecture Using Network Based Intrusion Prevention System - Ebiriene, PJ; ND, Nwiabu (International Journal of Computer Sciences and Engineering, 2019)
Cloud computing is a rapid rising technology and of a great degree acceptable computing prototype round the globe resulting from its merits on prompt deployment, monetary value (on staging up and environment), big storage capacity, likewise worry free privilege to system anytime, anywhere. This work is aimed at defining various attack patterns that affect the accessibility, confidentiality and integrity of resources and services in cloud computing environment. In addition, the research ushers in a network based intrusion prevention system (NIPS) to discover and stop suspecting actions by monitoring configuration of the system, logs files, network traffic changes, and activities of end-users in the cloud computing network using predefined signatures (rules). This rules classified IP address of users to white list for real user and blacklist for attacker. Results shows that block IP addresses found in blacklist were redirected to attackers (intruders) log, detailing the IP addresses, username, date/time and action. The system security is strong; users whose IP addresses, username and password were found in white list could use the system.